Drying Halves Decomposition Rates in River Networks by Decreasing Decomposer Diversity - Rubén del Campo; Thibault Datry; Arnaud Foulquier; Naiara López‐Rojo; Loïc Chalmandrier; Zoltán Csabai; David Cunillera‐Montcusí; Amaia A. Rodeles; Francisco J. Peñas; Bálint Pernecker; Núria Bonada; José Barquín; et al. (Global Change Biology, 2026)
River drying is intensifying worldwide due to climate change and increasing water abstraction, with major consequences for riverine biodiversity and ecosystem functioning. In river networks, drying not only alters local environmental conditions but also disrupts hydrological connectivity, reshaping the movement of organisms and resources at the river network scale. Leaf litter decomposition—a key ecosystem function in freshwater systems—is particularly sensitive to changes in the structure of decomposer communities. We hypothesized that spatiotemporal patterns of drying regulate decomposition by altering the diversity and composition of detritivorous macroinvertebrates, bacteria and fungi. We combined data from six European river networks spanning a wide latitudinal gradient to assess how local drying intensity and regional hydrological connectivity affect decomposition through changes in these decomposer groups. We found that short drying events (≤ 6 dry days) reduced decomposition rates by up to 50% mainly mediated by changes in the composition and diversity of decomposer communities. Drying decreased the diversity of groups contributing to decomposition, shifting the control of this function from a balanced contribution of fungi, bacteria and detritivores in perennial rivers to dominance by dry‐tolerant but less efficient bacteria in drying rivers. These community shifts persisted for months after flow resumption, causing sustained reductions in decomposition also in flowing conditions. Regional hydrological connectivity alleviated these negative effects of local drying by facilitating the recovery of more efficient aquatic decomposers. However, this effect depended on the river network. In more arid networks, stronger fragmentation hindered the recovery of decomposer communities after flow resumption. Overall, our results evidence that spatiotemporal patterns of drying can regulate the linkages between community structure and ecosystem functioning in river networks. As drying events become more frequent and prolonged, shifts in decomposers' diversity are likely to alter carbon cycling and energy fluxes in freshwater ecosystems under global change.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Functional plasticity of HCO3– uptake and CO2 fixation in Cupriavidus necator H16 - Justin Panich; Emili Toppari; Sara Tejedor-Sanz; Bonnie Fong; Eli Dugan; Yan Chen; Christopher J. Petzold; Zhiying Zhao; Yasuo Yoshikuni; David F. Savage; Steven W. Singer (Bioresource Technology, 2024)

Does the Southern Green Anaconda, Eunectes murinus, seek areas of high prey concentration in southeastern Peru? - Patrick S. Champagne; Thomas B. Herman; Paul Rosolie; Dylan Singer; Dan Horton; Carter J. Payne; Lucy Dablin; David Colville; Julio Cardenas; Miryam Quevedo; Trevor Avery; Renata Leite Pitman (Food Webs, 2024)

Unravelling the distribution of three Ammonia species (Foraminifera, Rhizaria) in French Atlantic Coast estuaries using morphological and metabarcoding approaches - Marie P.A. Fouet; Magali Schweizer; David Singer; Julien Richirt; Sophie Quinchard; Frans J. Jorissen (Marine Micropaleontology, 2024)

Unlocking foraminiferal genetic diversity on estuarine mudflats with eDNA metabarcoding - David Singer; Marie P.A. Fouet; Magali Schweizer; Aurélia Mouret; Sophie Quinchard; Frans J. Jorissen (Science of The Total Environment, 2023)

A framework for evaluating inherent biases within ship design tools - Michael J. Sypniewski; David J. Singer (Ocean Engineering, 2023)

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Correction to: A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Multilevel analysis of neuropathogenesis of neurocognitive impairment in HIV - Andrew J. Levine; Virawudh Soontornniyomkij; Cristian L. Achim; Eliezer Masliah; Benjamin B. Gelman; Janet S. Sinsheimer; Elyse J. Singer; David J. Moore (Journal of NeuroVirology, 2016)

Accelerated epigenetic aging in brain is associated with pre-mortem HIV-associated neurocognitive disorders - Andrew J. Levine; Austin Quach; David J. Moore; Cristian L. Achim; Virawudh Soontornniyomkij; Eliezer Masliah; Elyse J. Singer; Benjamin Gelman; Natasha Nemanim; Steve Horvath (Journal of NeuroVirology, 2016)

Beyond climate change attribution in conservation and ecological research - Camille Parmesan; Michael T. Burrows; Carlos M. Duarte; Elvira S. Poloczanska; Anthony J. Richardson; David S. Schoeman; Michael C. Singer (Ecology Letters, 2013)
There is increasing pressure from policymakers for ecologists to generate more detailed ‘attribution’ analyses aimed at quantitatively estimating relative contributions of different driving forces, including anthropogenic climate change ( ACC ), to observed biological changes. Here, we argue that this approach is not productive for ecological studies. Global meta‐analyses of diverse species, regions and ecosystems have already given us ‘ very high confidence’ [ sensu Intergovernmental Panel on Climate Change ( IPCC )] that ACC has impacted wild species in a general sense. Further, for well‐studied species or systems, synthesis of experiments and models with long‐term observations has given us similarly high confidence that they have been impacted by regional climate change (regardless of its cause). However, the role of greenhouse gases in driving these impacts has not been estimated quantitatively. Should this be an ecological research priority? We argue that development of quantitative ecological models for this purpose faces several impediments, particularly the existence of strong, non‐additive interactions among different external factors. However, even with current understanding of impacts of global warming, there are myriad climate change adaptation options already developed in the literature that could be, and in fact are being, implemented now.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Genetic resistance to diet-induced obesity in chromosome substitution strains of mice - Lindsay C. Burrage; Annie E. Baskin-Hill; David S. Sinasac; Jonathan B. Singer; Colleen M. Croniger; Andrew Kirby; E. J. Kulbokas; Mark J. Daly; Eric S. Lander; Karl W. Broman; Joseph H. Nadeau (Mammalian Genome, 2010)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

The chemical cell biology of zinc: structure and intracellular fluorescence of a zinc-quinolinesulfonamide complex - M. Sarwar Nasir; Christoph J. Fahrni; David A. Suhy; Kevin J. Kolodsick; Christopher P. Singer; T. V. O'Halloran (JBIC Journal of Biological Inorganic Chemistry, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)